(E)-2-((1,7,7-Trimethylbicyclo [2.2.1]Heptan-2-Ylidene) Amino) Acetic Acid Compound and their Metal Complexes: Synthesis and Characterization (Journal of the College of Basic Education, 2022)
The reaction of camphor with glycine under the showing conditions yielded (E)-2-((1,7,7-trimethylbicyclo[2.2.1]heptan-2-ylidene)amino)acetic acid ligand . The complexes of Cu(II), Ni(II), Co(II), Zn(II) and Fe(II) with ligand have been obtained by the reaction between copper bromide, hydrate nickel chloride, hydrate cobalt chloride, zinc chloride, and iron bromide with ligand in 1:2 mole ratio. The free ligands and their metal complexes have been separated in the solid state. The spectroscopic data of the complexes recommend their 1:2 structures which are researched by elemental analysis (CHN) 1H NMR and FT-IR spectroscopy. From the spectroscopic data proposed the octahedral structure for the all complexes.